High Signal Intensity on T2-Weighted MR Imaging at Term-Equivalent Age in Preterm Infants Does Not Predict 2-Year Neurodevelopmental Outcomes - Kidokoro, H.; Anderson, P.J.; Doyle, L.W.; Neil, J.J.; Inder, T.E. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: DEHSI on T2-weighted MR imaging in preterm infants at term-equivalent age has been regarded as an unfavorable marker for neurodevelopmental outcome. The aim of this study was to examine the relationship between the presence and extent of DEHSI and neurodevelopmental outcomes. MATERIALS AND METHODS: We evaluated the MR images of 160 preterm infants at term-equivalent age. The presence of DEHSI was evaluated in separate regions and classified into 5 grades based on the extent of DEHSI. We also examined within those infants with DEHSI, whether typical signal-intensity characteristics of the posterior periventricular crossroads region were visible. Finally, ADC and FA values within the white matter were analyzed. Neurodevelopmental outcomes were assessed at 2-year corrected age with a standardized neurologic examination and the BSID-II. RESULTS: The grade of DEHSI had significant linear trends with increasing ADC and a trend toward lower FA values. However, there was no relationship between the degree of DEHSI and 2-year neurodevelopmental outcomes. In contrast, 13 infants with DEHSI who did not have visible posterior crossroads had poorer neurodevelopmental outcomes compared with infants with visible posterior crossroads. CONCLUSIONS: Although DEHSI may represent disturbances in white matter structure, as illustrated by its relationship to altered ADC and FA values, there is no relationship to short-term neurodevelopment outcome unless there are invisible posterior crossroads, representing a severe form of global high T2 signal intensity. BSIDBayley Scales of Infant DevelopmentDEHSIdiffuse excessive high signal intensityFAfractional anisotropyMDIMental Developmental IndexPDIPsychomotor Developmental Index